Pemanfaatan Lahan Pekarangan Untuk Menciptakan “Kota Teduh” Tertata, Bernilai Ekonomi, Teredukasi Dan Hijau Di Kelurahan Srengseng Sawah - Sudarmin Parenrengi; Eka Sudarmadji; Fatima Tuzzahara A (SULUH: Jurnal Abdimas, 2019)
House can be utilized according to our tastes and desires. If it is managed with a bail yard, the house can provide benefits for family life. By planting productive plants in the yard will provide a double benefit. While creating a clean, green, healthy and beautiful environment. Every community organization needs the ability to survive in the face of today's changing environment. Therefore competent entrepreneurship training in the people of Srengseng Sawah Kelurahan must be conducted in order to be able to produce results in accordance with the goals and objectives and in accordance with the expected performance standards.